2020
DOI: 10.1155/2020/1250231
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Intra-Articular Osteotomy Using a 3D-Printed Model and Induced Membrane Technique for AO/OTA C3 Distal Femur Fracture with Articular Malunion and Metaphyseal Nonunion

Abstract: Comminuted distal femur fracture is a challenging injury, and care must be taken to reduce the articular fragment and acquire the sufficient stability for the metaphyseal comminution. We report the case of a AO/OTA C3-type distal femur fracture with articular malunion and metaphyseal nonunion. Articular malunion was treated with corrective osteotomy using a 3D-printed model for planning, and metaphyseal nonunion was treated with an induced membrane technique. Conclusion. Two major complications in the comminut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Further, personalized osteotomy guides have been recently proposed to provide better functional outcomes. Indeed, Saka et al 16 performed a corrective intraarticular osteotomy for an articular malunited distal femur fracture using a 3D-printed model and concluded that this method is helpful for the planning and evaluating the osteotomy. Sun et al 17 reported using 3D-printed navigation templates during minimally invasive percutaneous plate osteosynthesis of complex distal femoral fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Further, personalized osteotomy guides have been recently proposed to provide better functional outcomes. Indeed, Saka et al 16 performed a corrective intraarticular osteotomy for an articular malunited distal femur fracture using a 3D-printed model and concluded that this method is helpful for the planning and evaluating the osteotomy. Sun et al 17 reported using 3D-printed navigation templates during minimally invasive percutaneous plate osteosynthesis of complex distal femoral fractures.…”
Section: Discussionmentioning
confidence: 99%